جودة الحياة بين الرؤية الغربية والرؤية الإسلامية - بوساحة, بشير; فرطاس, ايمان (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة لبيان جودة الحياة في الرؤية الغربية والرؤية الإسلامية، ففي الغرب ارتبط مفهومها بالبعد الذاتي، والبعد الموضوعي. وقد طغت النزعة المادية على مضامين هذا المفهوم، فاستبعدت الجانب الديني، وجعلت الجانب الروحي مرادفا للجانب الوجداني. أما الرؤية الإسلامية فتدفع للجمع بين الجانب المادي والروحي ضمن البعد الموضوعي، ثم يأتي بعد الربانية للالتزام بالموقف الاسلامي فيما يتعلق بالبعدين السابقين. وتوصلت هذه الدراسة إلى أن الباحثين الغربيين يؤكدون على ضرورة الرضا بالأوضاع، والتمتع بكل لحظات السعادة مهما كانت العوائق. وهو ما يؤكد عليه الإسلام. وانطلاقا من بعد الربانية وعلاقتها بالبعدين الذاتي والموضوعي، يمكن أن تتحقق للفرد حياة طيبة وجودة الحياة. This study aims to highlight the quality of life in the Western vision and the Islamic vision. In the West, its concept is related to subjective dimension as well as the objective dimension. The materialism has dominated the contents of this concept, it deleted the religious side, and made the spiritual side closer with the emotional side. the Islamic vision, it urged to combine the objective dimension between the material side and the spiritual side, then comes the divine dimension to adhere to the Islamic position regarding the two previous dimensions. This study reached that Western researchers have become emphasizing the necessity of being satisfied with the situation, and enjoying all moments of happiness, regardless of the obstacles. Which is confirmed by Islam. Proceeding from the divine dimension and its relationship to the subjective and objective dimensions, a good and quality of life can be achieved for the individual.
Quality of life between the Islamic vision and the Western vision
مقال
Keywords: جودة الحياة ، الرؤية الاسلامية ، الرؤية الغربية، الربانية; Quality , life , Islamic vision , Western vision , lordship